The way of the wise : simple truths for living well - Leman, Kevin (Revell, 2013)
Dr. Kevin Leman shares the biblical wisdom that has shaped him into the successful, joy-filled person he is today. With his trademark wit and humorous stories from his personal life, Dr. Leman shows readers how to jump-start or revitalize their lives both spiritually and practically with words from one of the wisest men of all time. (Hint: It's not him.) Dr. Leman offers hope, courage, and a fresh perspective on living a great life.